MUPIROCIN RESISTANCE IN STAPHYLOCOCCUS AUREUS IN A TERTIARY CARE HOSPITAL OF SOUTH INDIA – A PROSPECTIVE STUDY - Venkatesh Bhavana, Malavalli; Joshi, Sangeeta; Adhikary, Ranjeeta; Beena, Hosdurg Bhaskar (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Mupirocin is a topical antibiotic used for the treatment of skin and soft tissue infections caused by Staphylococcus aureus and for the nasal decolonization of methicillin-resistant S. aureus (MRSA). The increasing reports of resistance to mupirocin are a matter of concern. We undertook this study to detect and differentiate the mupirocin resistance pattern and to analyze the susceptibility pattern among S. aureus isolates of our hospital. Methods: This is a prospective laboratory-based study conducted during the period May–September 2014. Clinical samples that grew S. aureus during the study period were tested for mupirocin resistance using the 5 μg and 200 μg discs. Minimum inhibitory concentration (MIC) detection of resistant strains was performed using the E-test. Results: Mupirocin resistance was seen in 4.81% of our S. aureus isolates; all of which exhibited high-level resistance with MIC ≥1024 μg/ml. Conclusions: The resistance is bound to rise with the increased usage of mupirocin; regular testing will help in tackling this upcoming problem and in preserving this important antibiotic against MRSA.